2005
DOI: 10.1111/j.1360-3736.2005.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the HR practices of an engineering institute with public sector industry for performance enhancement

Abstract: This study has been undertaken to compare the human resource development climate (HRDC) in an engineering institute with that of public sector industry in India, based on seven dimensions reflecting the nature of HRDC, and making suggestions to improve the HRDC in the institute. A sample size of 100 individuals each from the public sector and the institute was selected on a proportionate representative random sampling basis. Besides the mean and standard deviation, t‐test test has been carried out to test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Organizations try to increase their capabilities by investing more in training and management development and Ichniowski et al (1996) state that HRM practices have a greater effect on organizational performance than on individual performance. Moreover, human resource development encourages competency development by forming opportunities within the organization for employees to develop their competencies for both their own benefit and the benefit of others (Rao, 2000a;Rodrigues & Chincholkar, 2005). The competency-based approach has become integral in HRM during the last thirty years and, currently, different organizations, businesses and public services use competency models to better integrate global trends and business strategies with their human capital resources.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations try to increase their capabilities by investing more in training and management development and Ichniowski et al (1996) state that HRM practices have a greater effect on organizational performance than on individual performance. Moreover, human resource development encourages competency development by forming opportunities within the organization for employees to develop their competencies for both their own benefit and the benefit of others (Rao, 2000a;Rodrigues & Chincholkar, 2005). The competency-based approach has become integral in HRM during the last thirty years and, currently, different organizations, businesses and public services use competency models to better integrate global trends and business strategies with their human capital resources.…”
Section: Introductionmentioning
confidence: 99%
“…Employee competencies (EC) can be improved through effective training programs designed to subsequently enhance the employee overall performance. By gaining suitable knowledge, skills and attitude through training they can perform their current job more effectively and also prepare for future job (Rodrigues and Chincholkar, 2005). Rao (2000) revealed that employee competency has mediating effect between human resource management function and service quality among workers.…”
Section: Employee Trainingmentioning
confidence: 99%
“…A tendency at all levels starting from top management to the lowest level to treat the people as the most important resource; Perception that developing the competencies in the employees is the job of every manager/supervisor; faith in the capability of employees to change and acquire new competencies at any stage of life; a tendency to be open in communications and discussions rather than being secretive (fairly free expression of feelings); encouraging risk-taking and experimentation; making efforts to help nurses reorganize their strengths and weakness through feedback; a general climate of trust; a tendency on the part of nurses to be generally helpful to each other and collaborate with each other; team spirit; tendency to discourage stereotypes and favoritism; supportive personnel policies; supportive human resource development practices including performance appraisal, training, reward management, potential development, job-rotation career planning etc. [8] .…”
Section: Literature Review Hrd Climatementioning
confidence: 99%